The effect of different fish feed compositions on δ13C and δ15N signatures of sea bass and its potential value for tracking mariculture-derived nutrients. Issue 1 (2nd January 2018) - Kusche, Henrik; Hillgruber, Nicola; Rößner, Yvonne; Focken, Ulfert
ABSTRACT: Increasing demand for fish and seafood calls for an expansion of aquaculture production. At the same time, the status of the marine environment must not be jeopardised. Stable isotopes are potential markers for tracking feed-based nutrient flows from aquaculture into marine biota. Here, we demonstrate how four experimental diets (main protein components: fishmeal, soya protein concentrate, wheat gluten, and Jatropha kernel meal) and a commercial diet induce characteristic δ 13 C and δ 15 N signals in sea bass ( Dicentrarchus labrax ) during nine weeks of laboratory feeding under replicate conditions. The plant-protein-based diets containing wheat gluten and soya, and the commercial feed consistently induced the largest isotopic differentiation of the fish, both from the feed source and from the pre-experimental condition. The large difference of the fish on plant-protein-based diets compared to the range of natural isotopic variation in the macrozoobenthos of the North Sea lends support to the idea that plant-based feeds are suitable for tracing mariculture-derived organic matter under practical conditions. The commercial feed had a similar effect as the experimental feeds and would be a cost-effective option for an offshore aquaculture experiment.